A Randomised Controlled Phase II Trial of the Combination of XELOX with Thalidomide for the First-line Treatment of Metastatic Colorectal Cancer - Jing Lv; Ning Liu; Ke-wei Liu; Ai-ping Ding; Hao Wang; Wen-sheng Qiu (Cancer Biology & Medicine, 2012)
Objective To evaluate the efficacy and safety of the combination of XELOX regimen (oxaliplatin plus capecitabine) with thalidomide for the first-line treatment of metastatic colorectal cancer (MCRC). Methods All of the 89 patients with MCRC who fulfilled eligibility criteria were randomly assigned to treatment group (n=44) and control group (n=45). The treatment group received a combination of XELOX with thalidomide and the control group received XELOX alone. Each patient received at least 2 cycles of treatment (1 cycle=21 d). The primary endpoint was progression-free survival (PFS) and the secondary endpoints were objective response rate (ORR) as well as disease control rate (DCR). Drug safety and quality of life were also assessed. Results The median PFS of the treatment and control groups were 5.6 and 5.2 months, respectively. The difference did not have a statistical significance (P=0.307). The ORRs of the two groups also had no statistical difference (34.1% vs. 26.7%, P=0.446). The addition of thalidomide to XELOX significantly improved the DCR (63.6% vs. 42.2%, P=0.043). Among 24 patients with hepatic metastasis in the treatment group, 2 patients satisfied the surgical criteria after treatment but none of 23 patients in the control group did. Grade 3 or 4 constipation in patients treated with thalidomide was significantly increased (20.5% vs. 4.4%, P=0.022) but didn’t result in treatment interruption. The rate of lethargy was increased but the difference between the two groups had no statistical significance (13.6% vs. 4.4%, P=0.130). The quality of life had no statistical difference between the two groups. Conclusions The combination of XELOX with thalidomide for the first-line treatment of MCRC was well tolerated. Statistically significant improvement was achieved for the DCR but not for PFS.